Futurist Manifesto: action-text - Bortulucce, Vanessa Beatriz (Revista de Letras, 2010)
On the centenary of Futurism, this article focuses on the importance of the manifestos in the aesthetics of the group, investigating the relevance of the written text in the development of a global art, integrated into the human experience. Thus, we propose the manifesto should be seen as a medium that gathered all artistic experiences, the propeller of a new literature, one that is primarily action, gesture and destiny. Keywords: Italian Futurism. Aesthetics. Twentieth-Century Literature. Manifesto.